Zakon o dejavnosti zdravstvene nege - strokovna in normativna izhodišča - Starc, Andrej (Obzornik zdravstvene nege, 2001)
The article presents directives to elaborate a modern legislation in nursing care which will be usefull for users and executers of nursing care. Forming a modern and functional law of nursing care, adaptable in economic and social position in the country. The opinion of the International Council of nurses based on the analyses, standpoints and arguments declare, that the legislationin nursing care assurance a competence and autonomy of profession.
Keywords: European economic community; Legislation, nursing; Liability, legal; Nursing care; Pediatric nursing; Perinatal care; Poland; Psychiatric nursing; Standards; zakonodaja; zdravstvena nega